G24(P) Anxiety and chest pain: a chicken and egg situation?. (25th October 2020) - Doherty, L
Abstract : Introduction: Chest pain is a common paediatric presentation and can cause anxiety in patients, parents and healthcare professionals. Media coverage can heighten anxiety, but underlying cardiac pathology is rare in children. It is important to rule out serious underlying pathology and reassure appropriately. Case History: A 16 year old boy with Type 1 Diabetes Mellitus was referred by his diabetes nurse non-specifically unwell with hyperglycaemia and pallor. He had a two day history of anxiety associated with improving dyspnoea and chest pain, and was taking his GCSEs. He was fully immunised but had been given a recent telephone diagnosis of measles, and is needle phobic. On presentation, he was tachycardic with otherwise normal observations, and felt to be anxious. He became febrile and tachypnoeic with capillary blood gases showed a worsening non-ketotic metabolic acidosis, and a CRP of 80. He eventually agreed to a cannula under midazolam sedation 10 hours post attendance. He developed worsening central chest pain and dyspnoea which prevented him lying flat. An ECG and CXR were requested, however there was no ECG machine on the ward. Furthermore, nursing staff are not trained to record ECGs. On examination, he was pale, sweaty with a soft systolic murmur. His venous bloods showed a haemoglobin of 70, MCV 49 and platelets of 673. The ECG showed inferior ST elevation and inferolateral T wave inversion. A troponin was 1595 and an echocardiogram showed an akinetic inferior wall, dilated right heart, bright pericardium and no pericardial fluid. He was transferred to a tertiary adult cardiac centre, but due to the challenges with his diabetes and needle phobia, was moved to PICU under the paediatric cardiologists. A diagnosis of viral myocarditis was made causing left coronary inflammation, possibly exacerbated by microvascular disease secondary to diabetes, and anaemia. Conclusion: Always rule out serious pathology with a background of chest pain first, and be aware that anxiety may be a cause but also an effect of chest pain. Be aware of becoming task focused, and the risk of not seeing the bigger picture.